An audit of symptom triggered chlordiazepoxide treatment of alcohol withdrawal on a medical admissions unit. Issue 11 (21st October 2005) - Hardern, R; Page, A V
Abstract : Patients suffering from alcohol withdrawal were found on initial audit to be discharged before the resolution of their symptoms. A regimen using symptom triggered chlordiazepoxide was introduced and found, on re-audit and anecdotally, to be an improvement. The duration of symptoms was reduced significantly, the length of stay was reduced (although not statistically significant because of limited power), and most patients who had experience of both regimens found the symptom triggered regimen more effective.